2012
DOI: 10.2176/nmc.52.928
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Intracranial Aneurysms in Pediatric Polyarteritis Nodosa

Abstract: Polyarteritis nodosa (PAN) is a rare, systemic necrotizing vasculitis of small and medium size arteries that leads to aneurysms in various organs. Aneurysms associated with PAN are common in visceral arteries, however, intracranial aneurysms are rare, especially in childhood. A pediatric patient with PAN developed serial hemorrhagic strokes from a ruptured superior cerebellar artery aneurysm (subarachnoid hemorrhage) and a de novo aneurysm of the frontoorbital artery (intracerebral hemorrhage) after 9 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Large (>1.5 cm) PAN-associated IAs, such as in this case, are extremely rare,2 9 and this report represents the only giant (>2.5 cm) IA in the literature. IAs most commonly present with intracranial hemorrhage (SAH or, less frequently, ICH) 4 5 18 19. Ischemic strokes may occur, including retinal infarctions2 and a lateral medullary syndrome 6.…”
Section: Discussionmentioning
confidence: 99%
“…Large (>1.5 cm) PAN-associated IAs, such as in this case, are extremely rare,2 9 and this report represents the only giant (>2.5 cm) IA in the literature. IAs most commonly present with intracranial hemorrhage (SAH or, less frequently, ICH) 4 5 18 19. Ischemic strokes may occur, including retinal infarctions2 and a lateral medullary syndrome 6.…”
Section: Discussionmentioning
confidence: 99%
“…[176][177][178] Toyoda et al report the use of vascular intervention by way of aneurysm trapping for ruptured intracranial aneurysms in one pediatric patient. 179 In adult studies, Hashimoto et al demonstrated potential benefit with the use of plasmapheresis in addition to corticosteroids and cyclophosphamide in a case series, though Guillevin et al demonstrated no added benefit of plasmapheresis. 3,29,180 PAN is frequently relapsing and progressive despite treatment, and CNS involvement conveys a worse prognosis.…”
Section: Diagnosismentioning
confidence: 99%
“…[13][14][15][16] • Detachable balloons (Balt, Goldballoons, Balt Extrusion, Montmorency, France) are not currently Food and Drug Administration (FDA) approved, but are available in most countries, as of August 2014. • Care must be used when employing detachable balloons in the cerebral circulation, as they have the potential risk of spontaneously deflating over time or rupturing once deployed, and then embolizing into the distal arterial circulation.…”
Section: Mechanical Devicesmentioning
confidence: 99%